Validation of the BETA‐2 Score: An Improved Tool to Estimate Beta Cell Function After Clinical Islet Transplantation Using a Single Fasting Blood Sample. Issue 9 (21st April 2016) - Forbes, S.; Oram, R. A.; Smith, A.; Lam, A.; Olateju, T.; Imes, S.; Malcolm, A. J.; Shapiro, A. M. J.; Senior, P. A.
Abstract : The beta score, a composite measure of beta cell function after islet transplantation, has limited sensitivity because of its categorical nature and requires a mixed‐meal tolerance test (MMTT). We developed a novel score based on a single fasting blood sample. The BETA‐2 score used stepwise forward linear regression incorporating glucose (in millimoles per liter), C‐peptide (in nanomoles per liter), hemoglobin A1c (as a percentage) and insulin dose (U/kg per day) as continuous variables from the original beta score data set (n = 183 MMTTs). Primary and secondary analyses assessed the score's ability to detect glucose intolerance (90‐min MMTT glucose ≥8 mmol/L) and insulin independence, respectively. A validation cohort of islet transplant recipients (n = 114 MMTTs) examined 12 mo after transplantation was used to compare the score's ability to detect these outcomes. The BETA‐2 score was expressed as follows (range 0–42): BETA − 2 score = fasting C − peptide ( nmol / L ) × ( 1 − insulin dose [ units / kg ] ) Fasting plasma glucose ( mmol / L ) × HbA 1 c ( % ) × 1000 A score <20 and ≥15 detected glucose intolerance and insulin independence, respectively, with >82% sensitivity and specificity. The BETA‐2 score demonstrated greater discrimination than the beta score for these outcomes (p < 0.05). Using a fasting blood sample, the BETA‐2 score estimates graft function as a continuous variable and shows greater discrimination of glucose intolerance and insulin independence after transplantation versus the beta score, allowing frequent assessments of graft function. Studies examining its utility to track long‐term graft function are required. Abstract : Using regression analyses from the original Edmonton islet transplant recipients' fasting C‐peptide, fasting glucose, HbA1c and insulin requirements, the authors derive a new score of islet engraftment from a single fasting blood sample, then validate it in a separate cohort of islet transplant recipients.